2009
DOI: 10.1002/jrs.2442
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of conical intersections in resonance Raman intensities

Abstract: This paper deals with the manifestations of conical intersections (CIs), unequivocal spectroscopic signatures of which are still elusive, in the resonance Raman intensities. In particular, the results of our calculations on the 'two state-two vibrational mode' and the 'two state-three vibrational mode' models are presented. The models comprise two excited states of different spatial symmetry, one bright and one dark, which are coupled by a nontotally symmetric mode while the energy gap between them is tuned by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
4
1
Order By: Relevance
“…This is the first time that an S 3 (1)(ππ*)/S 2 (ππ*)conical intersection has been shown to exist near the FC region of the S 3 state of phthalide. This conical intersection, identified here by resonance Raman spectroscopy in conjunction with CASSCF calculations, is markedly different from the previously discovered S 3 (ππ*)/S 1 (nπ*) conical intersections for phthalide and other molecular systems …”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This is the first time that an S 3 (1)(ππ*)/S 2 (ππ*)conical intersection has been shown to exist near the FC region of the S 3 state of phthalide. This conical intersection, identified here by resonance Raman spectroscopy in conjunction with CASSCF calculations, is markedly different from the previously discovered S 3 (ππ*)/S 1 (nπ*) conical intersections for phthalide and other molecular systems …”
Section: Resultscontrasting
confidence: 99%
“…It is found that when the ab initio calculated resonance Raman intensities deviate greatly from the experimental values, the mixing of two states in the FC region is generally involved. More specifically, when abnormally intense experimental resonance Raman intensities appear in the non‐totally symmetric fundamental modes, they generally result from overtones and combination bands with the totally symmetric fundamental modes; therefore, a curve‐crossing or conical intersection must exist between the relevant excited states . In this case, Herzberg–Teller vibronic‐coupling theory and CASSCF calculations are used to determine the exact coupling states and the associated geometric structures of the curve‐crossing or conical intersection points.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with a previous theoretical study of the resonance Raman spectrum of pyrazine. 69,70 Here, we find that by measuring the vibrational frequencies of the reactant in the adiabatic ground and excited states as well as the electronic excitation energy, we can qualitatively estimate the value of the coupling constant λ between the electronic states using eq 3. Quantitative determination of λ requires explicit numerical simulations of the spectra as performed here.…”
Section: Probing the Interstate Coupling Near A Conical Intersection By Optical Spectroscopymentioning
confidence: 96%
“…Chowdary et al . used RR to study conical intersections; the unequivocal spectroscopic signatures of which are still elusive in RR intensities . They noted the importance of the pump excitation wavelength in femtosecond time‐resolved experiments that probe intersection‐induced nonadiabatic dynamics.…”
Section: Resonance Raman Spectroscopymentioning
confidence: 99%